Bacterial Adhesion on Soft Surfaces: The Dual Role of Substrate Stiffness and Bacterial Growth Stage - René Riedel; Garima Rani; Anupam Sengupta (Microorganisms)
The surface adhesion and stiffness of underlying substrates mediate the geometry, mechanics, and self-organization of expanding bacterial colonies. Recent studies have qualitatively indicted that stiffness may impact bacterial attachment and accumulation, yet the variation in the cell-to-surface adhesion with substrate stiffness remains to be quantified. Here, by developing a cell-level force–distance spectroscopy (FDS) technique based on atomic force microscopy (AFM), we simultaneously quantify the cell–surface adhesion and stiffness of the underlying substrates to reveal the stiffness-dependent adhesion of the phototrophic bacterium Chromatium okenii. As the stiffness of the soft substrate, modeled using a low-melting-point (LMP) agarose pad, was varied between 20 kPa and 120 kPa by changing the agarose concentrations, we observed a progressive increase in the mean adhesion force by over an order of magnitude, from <semantics>0.21±0.10</semantics> nN to <semantics>2.42±1.16</semantics> nN. In contrast, passive polystyrene (PS) microparticles of comparable dimensions showed no perceptible change in their surface adhesion, confirming that the stiffness-dependent adhesive interaction of C. okenii is of a biological origin. Furthermore, for Escherichia coli, the cell–surface adhesion varied between <semantics>0.29±0.17</semantics> nN and <semantics>0.39±0.20</semantics> nN, showing a weak dependence on the substrate stiffness, thus suggesting that stiffness-modulated adhesion is a species-specific trait. Finally, by quantifying the adhesion of the C. okenii population across different timescales, we reported the emergent co-existence of weak and strongly adherent sub-populations, demonstrating diversification of the adherent phenotypes over the growth stages. Taken together, these findings suggest that bacteria, depending on the species and their physiological stage, may actively modulate cell-to-surface adhesion in response to the stiffness of soft surfaces. While the surface properties, for instance, hydrophobicity (or hydrophilicity), play a key role in mediating bacterial attachment, this work introduces substrate stiffness as a biophysical parameter that could reinforce or suppress effective surface interactions. Our results suggest how bacteria could leverage stiffness-dependent adhesion and the diversity therein as functional traits to modulate their initial attachment to, colonization of, and proliferation on soft substrates during the early stages of biofilm development.